AKADEMIK LITSEYLAR O‘QUV JARAYONIDA MOBIL TEXNOLOGIYALARIDAN FOYDADANISHNING BA’ZI MASALALARI - Tursunov, S.Q.; Kadirov, U.E. (SCIENCE and SOCIETY, 2023)
In the article, the author revealed some issues of achieving efficiency using mobile technologies in the educational process of academic lyceums.